Participation of the Rural Women in the Group-Based Approach of the Cottage Industry Development Programme in Kuching, Sarawak - Mohd Hassan, Munirah (2005)
The purpose of this study was to explore the participation of the rural women in the group-based approach of the Cottage Industry Development Programme (CIDP) of the Ministry of Agriculture Sarawak. The participants of the study comprised members of the CIDP from the villages of Sejingkat, Buntal, Telaga Air and Selang Ulu located in Kuching District. Seventeen participants were purposefully selected and interviewed. The research questions for the study were: (i) How did the women start to get involved in the Programme? (ii) How was the Programme evolved? (iii) What did the women understand about the Programme? and (iv) Why did the women leave the Programme? The findings of this study were predominantly based on the qualitative methodology employed by the researcher. Guided by the constant comparative method and questions stipulated for this study, the findings revealed that participants joined the Programme because of (i) the need to make up the number to be eligible for the Programme; (ii)deference to the senior members and (iii) their interest in business and programme activity. Secondly, the findings revealed that none of the participants was involved in the formulation of the CIDP. Formulation of the CIDP was top-down rather than participative and participants were passive recipients rather than seen as partners. Thirdly, the findings revealed that there was lack of information and understanding of the concept and purpose of the Programme. Lastly, the findings revealed that participants left the Programme due to the main reasons of lack of incentives, absence of responsible leadership, lack of capacity and unfulfilled promises. Based on the findings of the study, it was concluded that: i. Participation in the CIDP was sustainable on a short-term basis only. ii. People's participation in the CIDP was seen only as beneficiaries of the programmes and not as one of partners. iii. There was lack of capacity of the CIDP,participants to run the Programme. iv. Capacity building and self-reliance were positive outcomes of the group approach of the CIDP. This study offers theoretical and practical applications for developing micro-enterprise programmes aimed at improving the socio-economic development of the rural women. A model of participation of rural women in micro-enterprise programme was developed. The model suggests that participants must first be equipped with the necessary knowledge and skills needed in entrepreneurship in ensuring sustainability of the participation of the rural women in a micro-enterprise programme.